Potential mechanisms regulating pulmonary pathology in inflammatory bowel disease. Issue 5 (25th August 2015) - Mateer, Sean W.; Maltby, Steven; Marks, Ellen; Foster, Paul S.; Horvat, Jay C.; Hansbro, Philip M.; Keely, Simon
Abstract : Review of mechanisms leading to pulmonary manifestations in IBD patients, including dysfunctional immune cell homing, microbial dysbiosis, and systemic inflammation. Abstract : Inflammatory bowel disease is associated with a number of comorbidities that arise at extraintestinal sites, including the lung. Pulmonary manifestations reported in inflammatory bowel disease include bronchiectasis, chronic bronchitis and importantly, a range of subclinical respiratory abnormalities that are often overlooked in routine clinical evaluation. Whereas evidence for the pulmonary manifestations of Inflammatory bowel disease is increasing, little is known about the immunologic and physiologic mechanisms regulating cross‐talk between the gut and lung during disease. This review examines reported lung involvement in Inflammatory bowel disease and discusses the possible immune pathways that underlie pulmonary pathologies. These mechanisms include dysfunctional immune‐cell homing, systemic inflammation, and microbial dysbiosis; all of which may contribute to Inflammatory bowel disease‐induced pulmonary inflammation. These mechanisms are discussed in the context of our current knowledge of the shared mucosal immune system and the immunology of Inflammatory bowel disease.